Clinical-epidemiological characteristics and surveillance in monitoring SARS-CoV-2 in the municipality of Teresopolis, RJ, Brazil (Research, Society and Development, 2022)
The high transmissibility of SARS-CoV-2 can be attributed to the unique virological characteristics of SARS-CoV-2. Early diagnosis is crucial to controlling the spread of SARS-CoV-2. The most common cardiovascular problems in patients with SARS-CoV-2 is acute myocardial injury. However, SARS-CoV-2 can cause direct and indirect cardiovascular sequelae, including acute coronary syndromes, cardiomyopathy, acute cor pulmonale, arrhythmias, and cardiogenic shock. Thus, as the disease progresses, there is a need for new clinical evidence based on epidemiological data and laboratory findings, and it is prudent to identify risk factors for the development of systemic complications associated with disease severity and may predict worse clinical outcomes. and increased mortality. The objective of the research is to evaluate and describe the clinical and epidemiological profile of SARS-CoV-2 cases, in order to assess the sociodemographic, clinical and epidemiological characteristics of individuals, seeking to subsidize the panorama of the spread of the disease, protection of the population through vaccination. , as well as the prevalence of diagnoses resulting from the virus in the city of Teresópolis - RJ, to assist in the understanding of the disease and its effects, so that solutions can be sought.